FGFR2 as A Prognostic and Predictive Marker in Colorectal Adenocarcinoma Based on TILs Grade - Andi Marcha Rianti; Muhammad Husni Cangara; Amalia Yamin; Haslindah Dahlan; Muhammad Riza Ilyasa; Upik Anderiani Miskad (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Colorectal cancer remains a serious health problem due to its high incidence and mortality rate each year. Histopathological grades and tumor-infiltrating lymphocytes (TILs) are associated with patient’s outcome. Fibroblast growth factor receptor 2 (FGFR2) overexpression is correlated with a worse prognosis in colorectal adenocarcinoma patients. Unfortunately, there are not many studies investigating the relationship between FGFR2 with histopathological grade and TILs in Indonesia. This study was conducted to analyze the correlation between FGFR2 expression with histopathological grade and TILs grade in colorectal adenocarcinoma.METHODS: Immunohistochemistry examination using FGFR2 rabbit polyclonal antibody was performed on 94 paraffin-embedded colorectal adenocarcinoma blocks and its expression was examined using a light microscope. The relationship between FGFR2 expression with histopathological grade and TILs grade in colorectal adenocarcinoma was statistically analyzed.RESULTS: Of the 94 samples examined, low grade adenocarcinoma was more common (n=76), of which 60.5% showed high FGFR2 expression. While in high grade adenocarcinoma, 83.3% of the samples showed high FGFR2 expression. In low grade TILs (n=30), 80% showed strong FGFR2 expression. While in high grade TILs (n=17), 64.7% showed weak FGFR2 expression. Based on statistical analysis, there was a significant correlation between FGFR2 expression and TILs grade (p=0.008). However, there was no significant association with histopathological grade (p=0.127).CONCLUSION: The significant correlation between FGFR2 expression and TILs grade suggests that FGFR2 may be used as a prognostic and predictive marker in colorectal adenocarcinoma.KEYWORDS: FGFR2, Colorectal adenocarcinoma, TILs, Histopathological grade